Primary medullary hemorrhage in a patient with coagulopathy due to alcoholic cirrhosis: A case report. Issue 14 (April 2018) - Shen, Guangxun; Gao, Yu; Lee, Kwee-Yum; Nan, Guangxian
Abstract: Rationale: Mild-to-moderate alcoholic cirrhosis of the liver is related to spontaneous intracerebral hemorrhage (ICH). In terms of spontaneous brainstem hemorrhage, pontine is considered as the most common site in contrast to medulla oblongata where the hemorrhage is rarely seen. This rare primary medullary hemorrhage has been attributed so far to vascular malformation (VM), anticoagulants, hypertension, hemorrhagic transformation, and other undetermined factors. Patient concerns: Herein, we describe a 53-year-old patient with 35-year history of alcohol abuse was admitted for acute-onset isolated hemianesthesia on the right side. He was normotensive on admission. A neurological examination revealed isolated hemihypoaesthesia on the right side. He had no history of hypertension, and viral hepatitis, and nil use of anticoagulants. Diagnoses: Brain computed tomography (CT) image demonstrated hemorrhagic lesion in dorsal and medial medulla oblongata which was ruptured into the fourth ventricle. Brain magnetic resonance imaging (MRI), and magnetic resonance angiography (MRA) demonstrated no evidence of VM. The laboratory tests implied liver dysfunction, thrombocytopenia, and coagulation disorders. Abdominal ultrasound, and CT image showed a small, and nodular liver with splenomegaly, suggestive of moderate alcoholic cirrhosis. Interventions: Liver protection therapy and the management of coagulation disorders. Outcomes: After 14 days, he was discharged with mild hemianesthesia but with more improved parameters in laboratory tests. At the 6-month follow-up, brain MRI, MRA, and non-contrast MRI showed no significant findings except for a malacic lesion. Lessons: We conclude that the patient had alcoholic cirrhosis with coagulopathy, and this may have resulted in primary medullary hemorrhage. This is a first case to report alcoholic cirrhosis as etiology of primary medullary hemorrhage.